Pernana Sektor Kelautan Dan Perikanan Dalam Pembangunan Wilayah Kota Tual Provinsi Maluku - Anna Kartika Ngamel; Ida I Dewa Ayu Raka Susanty (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2013)
Tual cityhasthe abundantmarine and fishery potencies because most ofthe region is the ocean.This study aimed to determine the contribution value of marine and fisheries sector to PDRB (GDP), to know the status or the level of the economic base of marine and fisheries sector in the city of Tual, and to formulate alternative development strategies of marine and fisheries sector in order to play a bigger role in the development of the Tualcity.  The result of this research indicated that the contribution value of marine and fisheries sector to PDRB (GDP) in Tual city gave a very big contribution in agricultural sector. The analysis of LQ indicated that the marine and fishery sector is said to bethe economic base sector  .Aglomeration analysis indicated that the sector activity of marine and fishery in Tual was not centralizedinvariousplacesaround Tual.  The calculation results of the specialization analysis on marine and fisheries sector inTual showed the unspecialized state.  It means that the marine and fisheries sector as not be enable to produce a particular fishery commodities. Therefore, the role from all elements is needed.  The effect of marine and fishery sector tend to fluctuate.  It was influenced by the economic condition after the region was divided. Based on the result of SWOT analysis. The three top priorities in choosing an alternative strategy of the development of marine and fisheries sector in Tual city are: 1) Promote cooperation between the government, employers and the public to utilize fishery and marine resources in a sustainable manner, 2) development of professional management in marine and fisheries resource; 3) Development of MCS system (Monitoring, Controlling and Surveillance) by related agencies.Keywords : Sector Marine and Fishery, PDRB, Economic Bases, Strategy Development.